Knowledge, attitude, and practice on school based sexual and reproductive education among teachers, in Jaffna Educational Zone, Jaffna - Jayasinghe, J.M.M.C.; Thabotharan, D.; Nithlavarnan, A. (4 th Undergraduate Research Symposium 2021, 2021)
Introduction and Objectives: Effective School-based sexual and reproductive education (SBSRE) can prevent adolescents’ sexual and reproductive health problems. The teacher plays the main role in imparting SBSRE. Even though SBSRE is a vital need, there was less importance given in South-Asian countries, including Sri Lanka. Therefore, this study aimed to assess the knowledge, attitude, practice, and association and correlation of practice with socio-demographic factors and attitude, of teachers’ on SBSRE, in Jaffna Educational Zone, Jaffna. Methods: A school-based descriptive cross-sectional study was carried out among the Science and Physical Education teachers (Grade 6-11) in Jaffna Educational Zone, through a self administered questionnaire, after obtaining permission from Ethics Review Committee. As it is a population study, no sampling method was used. Results: Among the total 212 population, respondents rate was 85.37% (31), the majority were Sri Lankan Tamil, females, ranged in age from 41-50. Respondents’ mean marks of knowledge, attitude, and practice were 73.34, 38.39, and 54.24 out of 100, respectively. Their practice was significantly associated with the educational qualification (p<0.001) and their attitude (r=0.439, p<0.001). The majority marked menstrual blood as polluted, masturbation as abnormal sexual behaviour, contraception was useless for the adolescents, and not participating in any program on SBSRE (149). Minority marked, abortion is legally accepted, and sex before age 14 was taken as rape, thus fewer marks on legal aspects of sexuality. The majority were not known Hepatitis b and Herpes simplex virus as Sexually Transmitted Diseases. Teachers have less practice on contraception, males’ teaching practice was higher than females, and the most preferred source of knowledge was books. Conclusion: Even though they have good knowledge, poor attitude and practice reduced the impartation of SBSRE. Thus, separate subjects, a clear curriculum, health-education programs to both teachers and community through health-sector, annual re-evaluation, and inspiration are recommended to enhance their attitude and practice towards SBSRE.
Keywords: School-based sexual and reproductive education (SBSRE); Knowledge; Attitude; Practice; Teachers